2023
DOI: 10.1002/hec.4645
|View full text |Cite
|
Sign up to set email alerts
|

Does affirmative action reduce disparities in healthcare use by Indigenous peoples? Evidence from Australia's Indigenous Practice Incentives Program

Abstract: Globally, Indigenous populations experience poorer health but use less primary healthcare than their non-Indigenous counterparts. In 2010, the Australian government introduced a targeted reform aimed at reducing these disparities. The reform reduced, or abolished prescription medicine co-payments and provided financial incentives for GPs to better manage chronic disease care for Indigenous peoples.Exploiting the framework of a natural experiment, we investigate how the reform affected these health disparities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…Further work is required to explore contributing factors to adherence issues in this population, however, these may include previously identified challenges such as misconceptions regarding medications and lack of culturally appropriate information sources [ 20 ]. Barriers to accessing care have been acknowledged by policymakers, with system level strategies implemented to improve access to medicines and healthcare for Indigenous Australians [ 40 ]. Conversely, adherence issues with psychotropic medications is well documented in people living with SPMI, with many factors, including the adverse effects of psychotropic medications such as those reported as MRPs in this current study, contributing to poor adherence [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further work is required to explore contributing factors to adherence issues in this population, however, these may include previously identified challenges such as misconceptions regarding medications and lack of culturally appropriate information sources [ 20 ]. Barriers to accessing care have been acknowledged by policymakers, with system level strategies implemented to improve access to medicines and healthcare for Indigenous Australians [ 40 ]. Conversely, adherence issues with psychotropic medications is well documented in people living with SPMI, with many factors, including the adverse effects of psychotropic medications such as those reported as MRPs in this current study, contributing to poor adherence [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the 2010 reforms increased use of primary care services and prescription medicines among Indigenous peoples (Trivedi and Kelaher 2020; Saxby et al 2023) and that hospitalisations associated with chronic conditions declined in areas with higher uptake of the reform (Trivedi et al 2017). While this reform has clearly reduce inequalities in primary healthcare, empirical research also suggests that they have had little to zero impact on access to specialist services (Saxby et al 2023). Further research on this is required to understand whether this is driven by reduced need for specialist care or reinforced substitution away from specialist care.…”
Section: Introductionmentioning
confidence: 99%
“…Despite innovative, responsive and culturally driven models of care, chronic conditions are a leading contributor to premature mortality among Indigenous peoples (Australian Indigenous HealthInfoNet, 2022; Brown 2012). Moreover, Indigenous peoples continue to experience barriers to engaging with mainstream healthcare, including a lack of culturally appropriate care, experiencing discrimination within the healthcare setting and scarce supply of specialist care (Marrone 2007; Hollinsworth 2010; Saxby et al 2023).…”
Section: Introductionmentioning
confidence: 99%